Authenticity and Parasocial Interaction in Influencer Marketing: An Integrated Systematic Literature Review of Consumer Outcomes and Theoretical Perspectives - Chairunnisaa M Z Huzaen (International Journal of Education Management and Religion, 2026)
Influencer marketing has become an increasingly important strategy in digital marketing, with authenticity and parasocial interaction emerging as key factors influencing consumer responses. Despite the growing body of literature, existing studies remain fragmented across different contexts and outcomes, making it difficult to obtain a comprehensive understanding of their roles in influencer marketing effectiveness. Therefore, this study aims to synthesize the existing literature on authenticity and parasocial interaction in influencer marketing through a Systematic Literature Review (SLR) using the PRISMA 2020 framework. A systematic search was conducted across relevant academic databases, resulting in 45 identified articles. Following the screening, eligibility assessment, and inclusion procedures, 20 articles were selected for final qualitative synthesis. The reviewed studies were analyzed using thematic analysis to identify major research trends, key themes, and research gaps. The findings reveal that authenticity and parasocial interaction play significant roles in shaping consumer behavior. Authentic influencers are generally perceived as more credible, trustworthy, and relatable, while parasocial interaction strengthens emotional connections between influencers and followers. These factors positively influence trust, engagement, purchase intention, electronic word-of-mouth (eWOM), and brand loyalty. Furthermore, the review highlights several gaps in the literature, including limited theoretical diversity, the dominance of cross-sectional survey designs, and the lack of studies examining virtual influencers and AI-generated influencers. This study contributes to the influencer marketing literature by providing an integrated theoretical perspective that connects authenticity, parasocial interaction, and consumer outcomes, thereby offering a more comprehensive explanation of influencer marketing effectiveness. The findings also provide practical implications for marketers by emphasizing the importance of selecting authentic influencers, fostering stronger influencer–consumer relationships, and developing engagement strategies that enhance trust, consumer loyalty, and positive word-of-mouth in digital environments